Intimate Partner Violence Risk Factors: A Vulnerability-Adaptation Stress Model Approach - Brunton, Robyn (Journal of interpersonal violence, 2024)
Intimate partner violence (IPV) disproportionally affects women. Using the vulnerability-adaptation stress model, we examined adverse childhood experiences (ACEs), self-esteem, and hope as vulnerability indicators and relationship status and length, positive and negative affect, and socioeconomic status (SES) as stressors to ascertain the risk for IPV. Women (N = 491, M = 37.15, standard deviation = 12.51) completed an online survey comprised of the Positive and Negative Affect Scale, Rosenberg’s Self-esteem Scale, Snyder’s Hope Scale, ACE questionnaire, Composite Abuse Scale Revised–Short Form, and demographic questions. Factor analysis identified four ACE factors of sexual abuse, physical or psychological abuse, witnessing domestic violence, and household dysfunction. A five-step hierarchical multiple regression identified that greater exposure to physical or psychological child abuse was associated with an increased risk of IPV (Step 2), B = 0.73 [0.16, 1.34]. Lower self-esteem, B = −0.30 [−0.47, −0.14] predicted IPV (Step 3). Age B = 0.07 [0.01, 0.13], negative affect, B = 0.39 [0.19, 0.59], and relationship length, B = −1.24 [−2.16, 0.41] were associated with a higher risk of IPV (Step 4). In Step 5, previous variables attenuated to non-significance while age, B = 0.07 [0.01, 0.13], negative affect, B = 0.39 [0.19, 0.59], and relationship length B = −1.25 [−2.16, 0.41] remained significant. While the key findings of this study were inconsistent with some commonly reported findings (e.g., ACEs, self-esteem, hope, relationship status, SES, age), these inconsistencies are important to highlight given the factorial approach to examining ACEs, the comprehensive analyses conducted, and our examination of these variables’ direct relationship to IPV. The study was limited by its cross-sectional nature, higher prevalence of IPV victims, and not examining IPV sub-types. Similar studies need to be conducted for other relationship types and victimized individuals (e.g., same-sex relationships and male victims) to provide a complete picture of risk factors for IPV.